Perlindungan Konsumen dalam Transaksi E-Commerce di Indonesia - Yolanda Wardiyanti (Badan Penerbit STIEPARI Press, 2024)
Advancements in technology have had a significant impact on commercial activities, particularly in the realm of online commerce, which facilitates the promotion, marketing, sale, and purchase of products or services through digital platforms. While these developments offer numerous benefits, they also raise concerns regarding potential violations of consumer rights. Law Number 8 of 1999 aims to ensure legal certainty in e-commerce transactions. The rapid growth of e-commerce in Indonesia provides convenience for consumers, but it also presents new challenges in terms of legal protection. This article examines the legal framework for consumer protection in e-commerce transactions in Indonesia, highlighting gaps in regulation and assessing the effectiveness of existing laws. A normative juridical approach is used to analyze various relevant legal instruments, including the Consumer Protection Law, the Law on Electronic Information and Transactions, and their implementing regulations. The findings indicate that, despite the existence of appropriate regulations, there are still shortcomings in law enforcement, consumer education, and dispute resolution mechanisms. This article recommends enhancing inter-agency cooperation, strengthening digital literacy among consumers, and improving dispute resolution systems to ensure comprehensive consumer protection in the e-commerce era.